2021
DOI: 10.1002/pc.26170
|View full text |Cite
|
Sign up to set email alerts
|

Natural rubber and copper alumina nanocomposite‐based flexible elastomer‐inorganic hybrid systems

Abstract: This work investigates the effect of different loading of copper alumina nanoparticles (Cu-Al 2 O 3 ) on the processing characteristics, crystalline, morphological, mechanical, and thermal properties of natural rubber (NR). The effective reinforcement of Cu-Al 2 O 3 nanoparticles into NR was carried out using a simple and efficient two roll mill mixing technique and the structural changes were systematically analyzed by Fourier transform infrared (FTIR), Xray diffraction (XRD), scanning electron microscope (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Thus, Cu–Al 2 O 3 has better electrical conductivity, thermal characteristics and mechanical properties than other metal oxides. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, Cu–Al 2 O 3 has better electrical conductivity, thermal characteristics and mechanical properties than other metal oxides. 12 …”
Section: Introductionmentioning
confidence: 99%
“…When the amount of NiO increases (10 phr) in Cl‐NR, the interparticle distances start to reduce which leads to a loosely packed and complex network structure resulting in an overlap of the immobile polymer segments and this result is in accordance with the previously reported work. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…4 b. Both spectra exhibited a broad amorphous region of natural rubber that is visible at 2θ = 18.13 ( Parvathi et al, 2021 ), and characteristic peaks of CaCO 3 were also identified in both spectra ( Lee et al, 2012 ). The intensity of the amorphous region decreased in the sample compared to pristine material.…”
Section: Degradation and Subproductsmentioning
confidence: 95%